THE ROLE OF TEACHERS IN DEVELOPING CRITICAL THINKING SKILLS: A SYSTEMATIC REVIEW (2020-2025) - Nargis Rashid (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Critical thinking is a fundamental skill that enables students to analyze, evaluate, and reflect on information to make reasoned decisions and solve complex problems. Teachers play a pivotal role in nurturing these skills through their instructional strategies, professional beliefs, and classroom practices. The study systematically reviews studies conducted from 2020 to 2025 to examine how teachers contribute to the development of critical thinking across educational settings. Using secondary data from empirical studies, review articles, and meta-analyses, the study identifies key teaching strategies, professional development practices, and institutional factors that influence students’ cognitive growth. Findings indicate that active learning approaches, including problem-based learning, Socratic questioning, collaborative learning, and reflective activities, significantly enhance critical thinking. Teacher beliefs, continuous professional development, and supportive institutional policies further strengthen these outcomes. Challenges such as rigid curricula, assessment pressures, and limited resources can impede effective implementation. The study highlights the need for an integrated approach combining capable teachers, innovative pedagogy, and conducive educational frameworks to cultivate critical thinking as a lifelong skill.